An Inside Sun: Lickanantay Volcanology in the Salar de Atacama - Ramos Chocobar, Sonia; Tironi, Manuel (Frontiers in Earth Science, 2022)
The need of establishing more substantive dialogs between the mainstream and Indigenous knowledge on volcanoes has been increasingly recognized. To contribute to this endeavor, in this article we present the basic volcanological understandings of the Lickanantay people in the Salar de Atacama Basin. The Salar de Atacama Basin is an active volcanic territory within the Central Volcanic Zone of the Andes (CVZA). From the El Tatio geothermal field to Socompa volcano, more than 19 active volcanoes surround the territory that the Lickanantay (Atacameño) people have inhabited for more than 11,000 years. Living around and with the geological dynamism of the CVZA for millennia, the Lickanantay communities have accumulated rich observational and ceremonial data on volcanoes and volcanism. Paradoxically, however, while the Atacameño people have thoroughly characterized the CVZA, the volcanology community has not been properly introduced to the ancestral knowledge articulated in the territory. In order to make traditional Atacameño perspectives on volcanoes, volcanic risk, and geo-cosmic interdependence more amply available to the volcanology community, in this article, we present a basic description of what we call Atacameño volcanology. By Atacameño volcanology, we understand the ancestral principles by which volcanoes are known and understood as partaking in larger processes of a cosmo-ecological formation. Specifically, we describe the basic volcanological notions arising from the Lickanantay ancestral knowledge—volcanic formation, functions, and behavior. Second, we focus on the El Tatio geothermal field to offer a situated example. Finally, we delineate some relevant elements of human–volcano interactions and volcanic risk management from an Atacameño perspective. In our conclusions we suggest that volcanology, particularly in the context of the Andes, needs to engage more substantially with the Atacameño or other ancestral systems of knowledge production to expand volcanological insights and respond to the call for decolonizing science.